Sosialisasi Upaya Peningkatan Kemampuan Bersaing UMKM di Era Digital Sekitaran Kota Pinang Kabupaten Labuhan Batu Selatan - Siregar, Zulkifli; Tarigan, Nur M Ridha; Nst, Venny Fraya Hartin; Wijaya, Doly Muhendy; Puspitasari, Ekas Mibari; Azaman, Azaman; Tumanggor, Boy Rizky (Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of the Community Service (PkM) activity, which involved socializing efforts to improve the competitiveness of MSMEs in the digital era, for residents of Pinang City, South Labuhan Batu Regency, was to raise awareness of the importance of starting MSMEs, how to develop MSMEs and digital marketing, and keep up with current developments. The socialization method was carried out in two stages: direct presentation of material and mentoring. Twenty MSME entrepreneurs participated in the activity. The results showed that the MSME Socialization successfully helped residents and MSME entrepreneurs gain knowledge on how to start MSMEs, how to develop MSMEs, how to market them, and how to use digital marketing to further increase sales turnover. Participants were able to understand the material related to MSMEs. Residents gained skills in using social media and sales websites for digital marketing. The satisfaction of the participants was evident in the high attendance and enthusiasm of the participants throughout the socialization activity.